High Plasma Exposure of Statins Associated With Increased Risk of Contrast-Induced Acute Kidney Injury in Chinese Patients With Coronary Artery Disease - Cai, Liyun; Bai, Xue; Lei, Heping; Wu, Hong; Liu, Yong; Zhu, Qian; Zhang, Shanshan; Liu, Yibin; Lin, Qiuxiong; Chen, Jiyan; Zhang, Bin; He, Guodong; et al. (Frontiers in Pharmacology, 2018)
The role of statins in reducing the incidence of contrast-induced acute kidney injury (CI-AKI) remains controversial. We sought to evaluate the association between CI-AKI and high plasma exposure of statins in coronary artery disease (CAD) patients undergoing coronary angiography (CAG). This association was first evaluated in 1219 patients with CAD receiving atorvastatin (AT) therapy and validated in 635 patients receiving rosuvastatin (RST) therapy. The plasma concentrations of statins were quantified using validated UPLC-MS/MS methods and CI-AKI incidence was assessed during the first 48 hours postoperatively. Among all participants (n =1854), AKI occurred in 57 of 1219 (4.7%) in the AT cohort and 30 of 635 (4.7%) in the RST cohort. High plasma AT-all exposure was associated with increased risk of CI-AKI (odds ratio [OR]: 2.265; 95% confidence interval [CI]: 1.609-3.187; p < 0.0001). Plasma AT-all concentration in the CI-AKI group (22.40 ± 24.63 ng/mL) was 2.6-fold higher than that in the control group (8.60 ± 9.65 ng/mL). High plasma RST exposure also significantly increased the risk of CI-AKI (OR: 2.281; 95% CI: 1.441-3.612; p = 0.0004). We further divided patients into two subgroups for each statin according to baseline renal function, and association between high plasma statin exposure and CI-AKI still remained highly significant in both subgroups. This study suggests for the first time that high plasma exposure of statins may significantly increase the risk of CI-AKI. Statins should be used with greater caution in CAD patients undergoing CAG to reduce the occurrence of CI-AKI.